Patent na piosenki. Wincentego Pola śpiew nie tylko z mogiły - Łoboz , Małgorzata (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2018)
This paper is an attempt at interpreting Wincenty Pol’s poetry, popularised in the form songs. Like most Romantic writers, the author of Pieśń o ziemi naszej regarded music as a unique dis-cipline of asemantic art, i.e. the one which goes beyond popular means of communication and capturing reality in a much deeper way than linguistic articulation. He believed that music is capable of expressing the essence of irrational and abstract phenomena: idealism, spirituality and transcendence; but - as a Romantic writer - he was also aware that art should, above all, reflect emotions accompanying human existence: love, loneliness, closeness, separation, suffering, joy and tears - as an emotional reaction to being moved. Some of his poems were included in Polish culture thanks to compositions by Fryderyk Chopin (performed, among others, by Delfina Potocka), Ignacy Komorowski, Julian Kapliński, Bolesław Dembiński, Adam Mũnchheimer and other composers. The popularity of those songs is the evidence that both folklore inspirations and accompanying historical circumstances recorded them in the na-tional song-book. They represent a typical model of ‘Romantic thinking’ and prove that the ‘Lied’ genre is treated as a return to the origins of culture, thus being an excellent example of lyrical miniatures, which can be fully interpreted by means of vocal realisation.